Standards of (In)coherence in Ancient Jewish Literature - Teeter, Andrew 1976-; Tooman, William A. 1969- (2020)
In this article, we sketch an anatomy of issues and decisions that must be navigated in any attempt to understand coherence and incoherence in ancient Jewish literature, including: the meaning of »coherence,« its relationship to »unity,« the suitability of modern standards of (in)coherence to ancient texts, and the availability of ancient standards of (in)coherence. We argue that modern perspectival representation and modern standards of literary (in)coherence are not necessarily appropriate to ancient Jewish literature, and we propose that these issues can only be properly approached after undertaking an inductive, comprehensive analysis of the ancient Jewish literature itself, in effect, learning the »ways of the text.«